Seal of Excellence - Menelaou, Melita (My University, 2026)
Certificate delivered by the European Commission - the institution managing Horizon 2020, the EU framework programme for research & innovation 2014-2020 [Horizon 2020’s Marie Skłodowska-Curie actions call H2020-MSCA-IF-2017]
Keywords: Sciences